Difference between revisions of "009B Sample Midterm 2, Problem 3"

From Math Wiki
Jump to navigation Jump to search
Line 12: Line 12:
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^2+x.</math> Then, <math style="vertical-align: -4px">du=(2x+1)~dx.</math>
+
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^2+x.</math> Then, <math style="vertical-align: -5px">du=(2x+1)~dx.</math> Thus,
 
|-
 
|-
 
|
 
|
::Thus, <math style="vertical-align: -12px">\int (2x+1)\sqrt{x^2+x}~dx\,=\,\int \sqrt{u}\,=\,\frac{2}{3}u^{3/2}+C\,=\,\frac{2}{3}(x^2+x)^{3/2}+C.</math>
+
::<math>\begin{array}{rcl}
 +
\displaystyle{\int (2x+1)\sqrt{x^2+x}~dx} & = & \displaystyle{\int \sqrt{u}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{2}{3}u^{3/2}+C}\\
 +
&&\\
 +
& = & \displaystyle{\frac{2}{3}(x^2+x)^{3/2}+C.}\\
 +
\end{array}</math>
 
|}
 
|}
 
'''Solution:'''
 
'''Solution:'''
Line 25: Line 31:
 
|We multiply the product inside the integral to get  
 
|We multiply the product inside the integral to get  
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -16px">\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt=\int_1^2 \bigg(8t^3-10+12-\frac{15}{t^3}\bigg)~dt=\int_1^2 (8t^3+2-15t^{-3})~dt</math>
+
|  
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt} & = & \displaystyle{\int_1^2 \bigg(8t^3-10+12-\frac{15}{t^3}\bigg)~dt}\\
 +
&&\\
 +
& = & \displaystyle{\int_1^2 (8t^3+2-15t^{-3})~dt.}\\
 +
\end{array}</math>
 
|}
 
|}
  
Line 33: Line 44:
 
|We integrate to get
 
|We integrate to get
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -16px">\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt=\left. 2t^4+2t+\frac{15}{2}t^{-2}\right|_1^2</math>.
+
|
 +
::<math style="vertical-align: -16px">\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt=\left. 2t^4+2t+\frac{15}{2}t^{-2}\right|_1^2.</math>
 
|-
 
|-
 
|We now evaluate to get
 
|We now evaluate to get
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -16px">\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt=2(2)^4+2(2)+\frac{15}{2(2)^2}-\bigg(2+2+\frac{15}{2}\bigg)=36+\frac{15}{8}-4-\frac{15}{2}=\frac{211}{8}</math>.
+
|
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt} & = & \displaystyle{2(2)^4+2(2)+\frac{15}{2(2)^2}-\bigg(2+2+\frac{15}{2}\bigg)}\\
 +
&&\\
 +
& = & \displaystyle{36+\frac{15}{8}-4-\frac{15}{2}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{211}{8}.}
 +
\end{array}</math>
 
|}
 
|}
  
Line 44: Line 63:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^4+2x^2+4</math>. Then, <math style="vertical-align: -5px">du=(4x^3+4x)dx</math> and <math style="vertical-align: -14px">\frac{du}{4}=(x^3+x)dx</math>. Also, we need to change the bounds of integration.  
+
|We use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^4+2x^2+4.</math> Then, <math style="vertical-align: -5px">du=(4x^3+4x)dx</math> and <math style="vertical-align: -14px">\frac{du}{4}=(x^3+x)dx.</math> Also, we need to change the bounds of integration.  
 +
|-
 +
|Plugging in our values into the equation <math style="vertical-align: -4px">u=x^4+2x^2+4,</math> we get <math style="vertical-align: -5px">u_1=0^4+2(0)^2+4=4</math> and <math style="vertical-align: -4px">u_2=2^4+2(2)^2+4=28.</math>
 
|-
 
|-
|Plugging in our values into the equation <math style="vertical-align: -2px">u=x^4+2x^2+4</math>, we get <math style="vertical-align: -5px">u_1=0^4+2(0)^2+4=4</math> and <math style="vertical-align: -4px">u_2=2^4+2(2)^2+4=28</math>.
+
|Therefore, the integral becomes
 
|-
 
|-
|Therefore, the integral becomes&nbsp; <math style="vertical-align: -14px">\frac{1}{4}\int_4^{28}\sqrt{u}~du</math>.
+
|
 +
::<math style="vertical-align: -14px">\frac{1}{4}\int_4^{28}\sqrt{u}~du.</math>
 
|-
 
|-
 
|
 
|
Line 58: Line 80:
 
|We now have:
 
|We now have:
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -16px">\int_0^2 (x^3+x)\sqrt{x^4+2x^2+4}~dx=\frac{1}{4}\int_4^{28}\sqrt{u}~du=\left.\frac{1}{6}u^{\frac{3}{2}}\right|_4^{28}=\frac{1}{6}(28^{\frac{3}{2}}-4^{\frac{3}{2}})=\frac{1}{6}((\sqrt{28})^3-(\sqrt{4})^3)=\frac{1}{6}((2\sqrt{7})^3-2^3)</math>.
+
|
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\int_0^2 (x^3+x)\sqrt{x^4+2x^2+4}~dx} & = & \displaystyle{\frac{1}{4}\int_4^{28}\sqrt{u}~du}\\
 +
&&\\
 +
& = & \displaystyle{\left.\frac{1}{6}u^{\frac{3}{2}}\right|_4^{28}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{1}{6}(28^{\frac{3}{2}}-4^{\frac{3}{2}})} \\
 +
&&\\
 +
& = & \displaystyle{\frac{1}{6}((\sqrt{28})^3-(\sqrt{4})^3)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{1}{6}((2\sqrt{7})^3-2^3).}\\
 +
\end{array}</math>
 
|-
 
|-
 
|So, we have  
 
|So, we have  
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -16px">\int_0^2 (x^3+x)\sqrt{x^4+2x^2+4}~dx=\frac{28\sqrt{7}-4}{3}</math>.
+
|
 +
::<math style="vertical-align: -16px">\int_0^2 (x^3+x)\sqrt{x^4+2x^2+4}~dx=\frac{28\sqrt{7}-4}{3}.</math>
 
|}
 
|}
  

Revision as of 13:52, 18 April 2016

Evaluate:

a)
b)


Foundations:  
How would you integrate
You could use -substitution. Let Then, Thus,

Solution:

(a)

Step 1:  
We multiply the product inside the integral to get
Step 2:  
We integrate to get
We now evaluate to get

(b)

Step 1:  
We use -substitution. Let Then, and Also, we need to change the bounds of integration.
Plugging in our values into the equation we get and
Therefore, the integral becomes
Step 2:  
We now have:
So, we have
Final Answer:  
(a)  
(b)  

Return to Sample Exam